Perancangan Sistem Informasi Manajemen untuk DistribuTion Requirement Planning - Annisa Kesy Garside (Department Industrial Engineering, University of Muhammadiyah Malang, 2001)
A cigaretec ompanyP, T. DjagungP adio fteng ot fouble or problemin distributionth eirproduct especially in acuracy of product delivery that cause lost sale. One of method that can beusedt o makea good deliverys cheduleis usingD istributionR equiremenPt lanning.lt makest heinformation of delivery schedule from factory to distribution or from distributor to company canbe fastly done and have high accuracy. It means that the company need a InformationManagement System ( SIM ).This research'sa ims in to designS IM and DRP in PT. DjagungP adi using thesemethod( systemt)h ef actoryc ans aveh oldingc ostl ack of productc osto f DjagungP adip roducta sDjagungP adi